농지의 정의 개선 및 식량위기시 농지활용방안 - 김홍상 (한국농촌경제연구원, 2006)
This study aims to reappraise the traditional concept of farmland from political and legal standpoints for confronting changes in the agricultural sector both home and abroad. It also seeks to find ways for the stable procurement and the efficient utilization of farmland during a food crisis by pursuing the benefits of a national economy through the modification of the concept and its scope, and finally review the concept's alternatives. Especially the concept of farmland in relation to the livestock feeding sites prescribed in the related laws is reviewed in view of political and legalistic interpretations. And some problems associated with the modification of the concept are drawn out. Furthermore, some schemes to solve those problems are considered. This study also investigates ways to utilize the farmland in case of emergency through domestic and foreign case studies and derives associated tasks in legal and institutional aspects. This study consists of two parts; the first part deals with the modification of the concept "farmland" in relation with livestock feeding sites, and the second part proposes schemes for efficient procurement and utilization of farmland in case of a food crisis. The first part examines the background and the progress being made in the discussions on the Agricultural Land Act revision, intended to include livestock feeding sites into the concept of farmland. The current system regarding livestock feeding sites is investigated, focusing on the regulation of farmland utilization and the farmland diversion system in addition to the concept itself. The main issues surrounding the concept modification are also discussed. Those investigations suggested improved alternatives to the concept of farmland so as to include livestock feeding sites and presented methods and tasks to make institutional reforms for implementing the alternatives. Lastly, general directions and major practical tasks aimed at improving its associated systems are proposed. The second part first identifies a distinct feature of this study that finds countermeasures to procure and utilize farmland in case of a food crisis. It tries to bring the conceptual ranges of a food crisis in unison based on previous research documents and classifies levels of a food crisis. It also presents countermeasures in line with major issues such as the utilization of existing farmland and the diversion of non farmland into crop areas. Lastly, for procurement and utilization of farmland in case of a food crisis, this study suggests improvements to the legal and institutional framework and related organizations. Researchers: Hong-Sang Kim(hskim@krei.re.kr) Jeong-Ho Kim(jhkim@krei.re.kr) Seok-Doo Park(sdpark@krei.re.kr)